Optical reconfiguration and polarization control in semi-continuous gold films close to the percolation threshold. Issue 33 (10th August 2017) - Frydendahl, Christian; Repän, Taavi; Geisler, Mathias; Novikov, Sergey M.; Beermann, Jonas; Lavrinenko, Andrei V.; Xiao, Sanshui; Bozhevolnyi, Sergey I.; Mortensen, N. Asger; Stenger, Nicolas
Abstract : fs-Laser pulses can be used to locally alter the morphology and optical properties of semi-continuous metal films in a simple laser writing process. Abstract : Controlling and confining light by exciting plasmons in resonant metallic nanostructures is an essential aspect of many new emerging optical technologies. Here we explore the possibility of controllably reconfiguring the intrinsic optical properties of semi-continuous gold films, by inducing permanent morphological changes with a femtosecond (fs)-pulsed laser above a critical power. Optical transmission spectroscopy measurements show a correlation between the spectra of the morphologically modified films and the wavelength, polarization, and the intensity of the laser used for alteration. In order to understand the modifications induced by the laser writing, we explore the near-field properties of these films with electron energy-loss spectroscopy (EELS). A comparison between our experimental data and full-wave simulations on the exact film morphologies hints toward a restructuring of the intrinsic plasmonic eigenmodes of the metallic film by photothermal effects. We explain these optical changes with a simple model and demonstrate experimentally that laser writing can be used to controllably modify the optical properties of these semi-continuous films. These metal films offer an easy-to-fabricate and scalable platform for technological applications such as molecular sensing and ultra-dense data storage.